Cedrus atlantica's Usability for Reducing and Monitoring the Change in Lithium Pollution in the Air - Kulaç, Şemsettin; Arıcak, Burak; Erdem, Ramazan (Kastamonu University, 2024)
The most important and harmful components of air pollution that affect the health and cause the death of millions of people every year around the world are heavy metals. Due to their potential harm, monitoring the change in the concentration of heavy metals in the air and reducing pollution are essential. This study aimed to determine the usability of Cedrus atlantica grown in Düzce, where heavy metal pollution is reported to be high, for monitoring and reducing the change in lithium pollution in the air. For this purpose, the change in Li concentration in Cedrus atlantica annuals grown in Düzce was evaluated in the 60-year period. As a result of the study, it was determined that Li pollution in the region has increased significantly in the last decade. The highest values were generally obtained in the north direction, and this result was interpreted as Li concentration originating from the highway in this direction, i.e., traffic. As a result of the study, Cedrus atlantica is a very suitable species for monitoring and reducing the change in Li pollution.
Keywords: Heavy metal|Lithium|Biomonitor|Cedrus atlantica|Düzce|Ağır metal|Lityum|Biomonitor|Cedrus atlantica|Düzce